2021
DOI: 10.5070/p537253242
|View full text |Cite
|
Sign up to set email alerts
|

A recreation ecology perspective on the COVID-19 (SARS-CoV-2) pandemic: Potential parks and protected area impacts relating to visitor spatial use, terrestrial flora and fauna, and management

Abstract: Measures to limit the spread of COVID-19 require changes in the ways that people travel, gather, and recreate in outdoor spaces. In 2020, to limit human-to-human transmission of COVID-19, US park and protected area managers at all levels of governance implemented closures and restrictions on the types of activities and facilities available for public use. At the same time, the US Centers for Disease Control and Prevention outlined suggestions for social distancing, wearing face masks, and limiting travel and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…These respondents changed their travel plans, and noted coping behaviors, such as arriving earlier, going to different areas of the park, exploring fewer sites, engaging in more automobile touring rather than non-motorized outdoor recreation, or ending a visit earlier than planned. These self-reported behaviors amid the pandemic are in accord with the predictions and observations of other protected area researchers (Jacobs et al 2021;Schneider et al 2021), who found that visitor coping behaviors were the result of attempting to social distance, avoid areas where masks were not being worn at a level comfortable to the respondent, or avoid crowding in general.…”
Section: Discussionsupporting
confidence: 86%
“…These respondents changed their travel plans, and noted coping behaviors, such as arriving earlier, going to different areas of the park, exploring fewer sites, engaging in more automobile touring rather than non-motorized outdoor recreation, or ending a visit earlier than planned. These self-reported behaviors amid the pandemic are in accord with the predictions and observations of other protected area researchers (Jacobs et al 2021;Schneider et al 2021), who found that visitor coping behaviors were the result of attempting to social distance, avoid areas where masks were not being worn at a level comfortable to the respondent, or avoid crowding in general.…”
Section: Discussionsupporting
confidence: 86%
“…This study analyzed research papers that examined the diverse impacts of COVID-19 on protected areas. Regarding management of conserved areas, the impacts of the pandemic on decisions and strategies had cascading implications on economic, social, and ecological aspects (Jacobs et al, 2021). On operation levels, protected areas had to modify their daily routines and postpone activities that did not comply with lock-down restrictions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Visitor flow patterns had multiple effects on visitors' experience, on local economies, on the tourism industry, on park's funding and human interaction with flora and fauna (Cheablam, Dachyosdee & Purintarapiban, 2021;Jacobs et al, 2021;Mandić, 2021;Cahyadi & Newsome., 2021;McGinlay et al, 2020). The effectiveness of visitor management was disrupted as problems on overcrowding and carrying capacity appeared.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased human presence in forests has altered the movement patterns of wild animals [24]. Other possible implications include increased soil erosion on steeper slopes, changes in plant communities due to trampling, soil compaction and trail widening, and uncharacteristic animal behaviour due to littering, all reported in nature areas both in Europe and overseas [25][26][27].…”
Section: Introductionmentioning
confidence: 99%